2017
DOI: 10.1080/00986445.2015.1065820
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Adsorption Studies of Tetracycline onto Various Types of Adsorbents

Abstract: Over the past few decades, the usage of antibiotics is growing on a rapid phase. The continuous use in the treatment against several bacterial infections paves a way to increased resistant strains. Environmental pollution created by antibiotics is considered as a serious problem though no toxic reports were known until now. The pharmaceutical compounds present in the environment are known as "Emerging Pollutants." Among antibiotics tetracycline (TET) class of drugs were known to exist for several years.Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(18 citation statements)
references
References 100 publications
0
17
1
Order By: Relevance
“…reported that graphene loaded with 40% nanorod MnO 2 exhibits a maximum TC adsorption capacity ( q m ) of 1789 mg/g and that the observed adsorption capacity remains constant with increasing MnO 2 loadig from 40% to 60% 31 . In our study, P0.2 showed a desirable TC q m of 2613.3 mg/g, which is higher than those of P0, 40% MnO 2 -loaded graphene 31 , carbon materials (maximum of 1340.8 mg/g) 30 and zeolite materials (800 mg/g) 19 . P0.2 also showed a TC removal rate higher than those of other flocculants (Fig.…”
Section: Resultscontrasting
confidence: 50%
See 2 more Smart Citations
“…reported that graphene loaded with 40% nanorod MnO 2 exhibits a maximum TC adsorption capacity ( q m ) of 1789 mg/g and that the observed adsorption capacity remains constant with increasing MnO 2 loadig from 40% to 60% 31 . In our study, P0.2 showed a desirable TC q m of 2613.3 mg/g, which is higher than those of P0, 40% MnO 2 -loaded graphene 31 , carbon materials (maximum of 1340.8 mg/g) 30 and zeolite materials (800 mg/g) 19 . P0.2 also showed a TC removal rate higher than those of other flocculants (Fig.…”
Section: Resultscontrasting
confidence: 50%
“…The adsorption capacity of the erdite nanorods for TC was investigated because the latter is a common pollutant in pharmaceutical wastewater 19,29 . Four of the most widely established isotherm models, namely, the Langmuir (Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GPs could serve as controllable, cost-effective, and synthetic aluminosilicate materials for minimizing and removing pathogenic material, such as toxins, from patient infection sites, improving patient outcomes and reducing reliance on antibiotics. While the adsorption of antibiotics with GPs is a potential concern for infection treatment, GP-mediated antibiotic removal in hemodialysis cases (Holubek et al, 2008) and in poultry, agricultural, environmental, and aquaculture settings, where pharmaceutical compounds are considered emerging pollutants (McClellan and Halden, 2010;Done and Halden, 2015;Priya and Radha, 2017;Tang et al, 2017), and in drug delivery applications (Lopes et al, 2014) could be greatly beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…TCs are among the most used antibiotics both within therapeutic and veterinary rehearsals. For veterinary purposes only, 2500 tons are consumed annually in Europe [ 8 ]. As per the reported risk quotient (RQ) [ 3 ], tetracycline (the parent drug) is among the 14 pharmaceuticals posing a high risk to the environment.…”
Section: Introductionmentioning
confidence: 99%